IDENTIFIKASI JAMUR PATOGEN PENYEBAB PENYAKIT PADA TANAMAN PADI (Oryza sativa) DI LUBUK RUSO KECAMATAN PEMAYUNG KABUPATENBATANGHARI JAMBI - Yuza Defitri (Jurnal Ilmiah Universitas Batanghari Jambi, 2013)
The research about identification of pathogenic fungi in rice plant (Oryza sativa) di Lubuk Ruso Kecamatan Pemayung Kabupaten Batanghari Jambi and Agriculture Quarantine Laboartory Jambi has been done for five months. The aim of research is to identificated disease in rice plants (Oryza sativa) that caused by fungi in Lubuk Ruso Kecamatan Pemayung Kabupaten Batanghari Jambi. The research  maked to see disease sign in rice plants area and to identificated pathogenic fungi in laboratory by microscop and fungi identifications book.The result of this research indicated that find four pathogenic fungi to attack rice plants in Lubuk Ruso Kabupaten Batanghari that is: 1) Pyricularia oryzae  fungi caused Blas disease, 2) Drechslera oryzae fungi caused Brown spot disease,            3) Curvularia sp fungi caused Curvularia disease and 4) Alternaria sp fungi caused   Stacburn disease. Key words : Identification, Patogenic fungi and Oryza sativa